Is my wound infected? A study on the use of hyperspectral imaging to assess wound infection - Ramirez-GarciaLuna, Jose L.; Martinez-Jimenez, Mario A.; Fraser, Robert D. J.; Bartlett, Robert; Lorincz, Amy; Liu, Zheng; Saiko, Gennadi; Berry, Gregory K. (Frontiers in Medicine, 2023)
Introduction: Clinical signs and symptoms (CSS) of infection are a standard part of wound care, yet can have low specificity and sensitivity, which can further vary due to clinician knowledge, experience and education. Wound photography is becoming more widely adopted to support wound care. Thermography has been studied in the medical literature to assess signs of perfusion and inflammation for decades. Bacterial fluoresce has recently emerged as a valuable tool to detect high bacterial load within wounds. Combining these modalities offers a potential objective screening tool for wound infection.A multi-center prospective study of 66 outpatient wound care patients used hyperspectral imaging to collect visible light, thermography, and bacterial fluorescence images. Wounds were assessed and screened using the International Wound Infection Institute (IWII) checklist for CSS of infection. Principal component analysis was performed on the images to identify wounds presenting as infected, inflamed, and non-infected.The model could accurately predict all three wound classes (infected, inflamed, and noninfected) with an accuracy of 74%. They performed best on infected wounds (100% sensitivity and 91% specificity), compared to non-inflamed wounds (sensitivity 94%, specificity 70%) and inflamed wounds (85% sensitivity, 77% specificity).Discussion: Combining multiple imaging modalities enables the application of models to improve wound assessment. Infection detection by CSS is vulnerable to subjective interpretation and variability based on clinicians' education and skills. Enabling clinicians to use point-of-care hyperspectral imaging may allow earlier infection detection and intervention, possibly avoiding delays in healing and adverse events.